Effect of Complement on HIV-2 Plasma Antiviral Activity Is Intratype Specific and Potent - Özkaya Şahin, Gülşen; Holmgren, Birgitta; Sheik-Khalil, Enas; da Silva, Zacarias; Nielsen, Jens; Nowroozalizadeh, Salma; Månsson, Fredrik; Norrgren, Hans; Aaby, Peter; Fenyö, Eva Maria; Jansson, Marianne (Journal of Virology, 2013)
Article Usage Stats Services JVI Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue Spotlights in the Current Issue JVI About JVI Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JVI RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0022-538X Online ISSN: 1098-5514 Copyright © 2014 by the American Society for Microbiology. For an alternate route to JVI .asm.org, visit: JVI